Developmental stages, incubation temperature, and in vivo traceability of primordial germ cell in an important aquaculture species Piaractus mesopotamicus - Zacheo Coelho, Geovanna Carla [UNESP]; Arashiro, Dilberto Ribeiro [UNESP]; Disselli, Tamiris; Pereira-Santos, Matheus; Mira-Lopez, Tatiana Maria; Monzani, Paulo Sergio; Senhorini, Jose Augusto [UNESP]; Fujimoto, Takafumi; Yasui, George Shigueki [UNESP] (Elsevier B.V., 2021)
This study aims to describe the early development of Piaractus mesopotamicus in detail at 22 degrees C, 26 degrees C, and 30 degrees C and describe primordial germ cell migration in vivo by using artificial GFP-nos1 3'UTR mRNA for future application in surrogate technology. The highest hatching rate was observed at 26 degrees C with 52.9 +/- 18.9%, which was considered the best incubation temperature. At 22 degrees C, the embryos survived only until the blastula stage. The first visualization of PGCs occurred in the segmentation period when the embryos presented between 6 and 16 somites. The number of GFP-positive cells varied from 7 to 18 per embryo (mean 11.2; n = 15). After hatching, the GFP-positive cells ranged from 7 to 22 per embryo (mean 14.6; n = 15). The PGCs were traced until the 9th day after hatching. The obtained data allow for the incubation temperature manipulation and early development and traceability of PGCs, which are important for reproductive biotechniques, establishment of cryobanks, and subsequent reconstitution through a germline chimera.
Keywords: PGC; Embryonic development; Biotechnology; Germline chimera; Temperature; Incubation